Menyingkap Rahasia Makna Salawat: Interpretasi dalam Al-Qur’an Studi terhadap Kitab Al-Jailani - Cahya, Annisa Dwi; Andy, Safria; Rambe, Uqbatul Khoir (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This research aims to reveal the secret meaning of salawat in the Qur'an and find out how and how the Al-Qur'an interprets the study of the book Al-Jailani. This research is qualitative and is a type of library research. Meanwhile, the data analysis method used is the descriptive analysis method. The research results show that (1) in the Koran, the researchers found Surah al-Ahzab 56 that Sheikh Abdul Qadir al-Jailani, in his interpretation, explained that salawat is a form of respect and glorification. (2) the form of respect here is believing in all the truths of the Prophet. glorify it, stay away from what Allah and the Messenger forbade. (3) the word respect here enters into human beings, namely humans whose names and characteristics of God are reflected in their entirety and who have the knowledge to reach the highest level of consciousness towards God.